Using Games and Interactive Methods in Foreign Language Teaching - Usmanova , Nodira (The Lingua Spectrum, 2025)
This article discusses the importance of games and interactive methods in foreign language teaching. Game-based methods help increase students’ motivation, expand their vocabulary, and develop practical skills. Role-playing games, word games, and team competitions make the language learning process more engaging. Interactive methods ensure active student participation and enhance their communication skills. Additionally, the article provides recommendations for effectively applying these methods.